Increasing Rosella Farmers Capacity by Double Diamond Design Thinking Approach - Pribadi, Florence; Kartikawati, Muliasari; Njoto, Juli Karijati; Sari, Nurul Illahi Kusuma; Nur, Farah Shania (ASEAN Journal of Community Engagement, 2022)
Rosella (Hibiscus sabdariffa Linn) is a well-known family medicinal plant (Toga). Spoilage due to the weather, and the consequent low revenue gained from selling dried rosella are two of the main challenges currently being encountered by rosella farmers. Regardless of previously practicing community engagement including regular training from local authorities, farmers are still encountering difficulties to implement the training materials, consequently experiencing loss. Method incorporated in this community engagement is the double diamond design thinking that ensures putting the farmers first in all stages. Method chosen for drying rosella was a mixed solar dryer equipped with heating lamps and a blower. In addition, a new revenue generating skill was also introduced which included making rosella soap, as the farmers already had access to most of the tools and was a relatively easy process to follow. Farmers were equivalently encouraged to implement the acquired new knowledge as they were involved in every decision-making process, which increased their sense of belonging. After the solar dryer was installed, there were no more spoiled products, and the dried rosella yield was more vibrant in color and shape. Soap production has high conditioning effects and carries potential to bring better revenue compared to selling dried rosella petals. Community intervention can be more fruitful by involving community partner since conception. This program has surpassed the target and partner are happily and willingly continuing the project. This method can be used by other community empowerments doers, especially in horticultural field, as a model for improved farmer knowledge and increased yield, and in the long run to improve national food security.